S = 0 . 1 + 0 . 0 2 + 0 . 0 0 3 + 0 . 0 0 0 4 + ⋯ + 1 0 n n + ⋯
Given that the infinite sum S can be expressed as b a , where a and b are coprime positive integers, find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There are Millions of methods to solve this question, I think this is the simplest
S = 0 . 1 2 3 4 5 ⋯ 1st Equation 1 0 S = 1 . 2 3 4 5 6 ⋯ 2nd Equation Subtract the two equations 9 S = 1 0 × 0 . 1 1 1 1 ⋯ S = 9 1 0 × 9 1 = 8 1 1 0
yes bro , i did the same (exactly) way!! you are awesome!
Log in to reply
Thank you :)
Log in to reply
what is the difference between metrix and determinant methods to solve a system of equations. because my teacher crossed whole question because of that , plz tell.
Log in to reply
@A Former Brilliant Member – i know only the determinant method to solve system of equations :/
S = 0 . 1 + 0 . 0 2 + 0 . 0 0 3 + 0 . 0 0 0 4 + . . .
S = ( 0 . 1 ) + 2 ( 0 . 1 ) 2 + 3 ( 0 . 1 ) 3 + 4 ( 0 . 1 ) 4 + . . .
Let x = 0 . 1 , then:
S = x + 2 x 2 + 3 x 3 + 4 x 4 + . . .
S = x + 3 x 2 − x 2 + 4 x 3 − x 3 + 5 x 4 − x 4 + . . .
S = x + ( 3 x 2 + 4 x 3 + 5 x 4 + . . . ) − ( x 2 + x 3 + x 4 + . . . )
S = x + ( d x d x 3 + d x d x 4 + d x d x 5 + . . . ) − ( x 2 + x 3 + x 4 + . . . )
S = x + d x d ( x 3 + x 4 + x 5 + . . . ) − ( x 2 + x 3 + x 4 + . . . )
Since x = 0 . 1 , both x 3 + x 4 + x 5 + . . . and x 2 + x 3 + x 4 + . . . are infinite geometric progressions. ( ∣ r ∣ = 0 . 1 < 1 ) . Hence:
S = x + d x d ( 1 − x x 3 ) + 1 − x x 2
S = ( 1 − x ) 2 x
S = ( 1 − 0 . 1 ) 2 0 . 1 = 8 1 1 0 ⟹ a + b = 9 1
We have,
S = 1 0 1 + 1 0 2 2 + 1 0 3 3 + ⋯ ∞ − 1 0 S = 1 0 2 1 + 1 0 3 2 + 1 0 4 3 + ⋯ ∞ Shifting each term one place to the right ______________________________________________ 1 0 9 S = 1 0 1 + 1 0 2 1 + 1 0 3 1 + 1 0 4 1 ⋯ ∞ ______________________________________________ ⟹ 1 0 9 S = 1 − 1 0 1 1 0 1 Using S ∞ = 1 − r a , w h e r e ∣ r ∣ < 1 ⟹ 1 0 9 S = 9 1 ⟹ S = 8 1 1 0 = b a ∴ a = 1 0 and b = 8 1
Hence, a + b = 9 1
We have to find:
⟹ 1 0 1 + 1 0 0 2 + 1 0 0 0 3 + . . .
Using Arithmetic-Geometric progression .
⟹ ( 1 0 1 ) ( 1 + 1 0 2 + 1 0 0 3 + . . . )
Here a = 1 , d = 1 and r = 1 0 1 .
= ( 1 0 1 ) ( 1 − 1 0 1 1 + ( 1 − 1 0 1 ) 2 1 × 1 0 1 )
⟹ 1 0 1 × 8 1 1 0 0 = 8 1 1 0
∴ a + b = 1 0 + 8 1 = 9 1 .
I also did the same way using the formula S ∞ = 1 − r a + ( 1 − r ) 2 d r
I tried a telescoping series approach on a finite version of the sum then applied the limit as k approaches infinity:
So, the sum a+b is 91.
Problem Loading...
Note Loading...
Set Loading...
S = 0 . 1 + 0 . 0 2 + 0 . 0 0 3 + 0 . 0 0 0 4 + … 1 0 S = 1 + 0 . 2 + 0 . 0 3 + 0 . 0 0 4 + … − S = − 0 . 1 − 0 . 0 2 − 0 . 0 0 3 − 0 . 0 0 0 4 … 9 S = 1 + 0 . 1 + 0 . 0 0 1 + 0 . 0 0 0 1 + 0 . 0 0 0 0 1 + … The above is in geometric progression where a 1 = 1 , r = 1 0 1 Therefore as GP tends to infinity 9 S = 1 − r a 1 9 S = 1 − 1 0 1 1 9 S = 1 0 1 0 − 1 1 9 S = 9 1 0 S = 8 1 1 0 Therefore the answer is 10 + 81 = 9 1